USER EXPERIENCE AND ACCESSIBILITY IN COLLEGE LIBRARIES: ANALYZING CHALLENGES AND EXPECTATIONS - Shukla, Ganesh Dutt; Mishra, Shesh (International Journal of Research -GRANTHAALAYAH, 2025)
College libraries serve as vital academic hubs, providing essential resources for students, faculty, and researchers. However, challenges such as outdated collections, limited digital resources, slow internet connectivity, and insufficient ICT-based services hinder their accessibility and effectiveness. This study examines user experiences, accessibility issues, and service efficiency across 33 college libraries, analyzing the frequency of library visits, satisfaction levels, and user expectations. The findings reveal that while book lending services remain satisfactory, digital resource availability, inter-library loan services, and mobile-based facilities require significant improvement. Users emphasize the need for better internet connectivity, expanded digital collections, automation of services, and IT training to enhance accessibility. The study underscores the urgency for modernization and user-centered policies to transform libraries into dynamic, technology-driven spaces. Addressing these gaps will ensure libraries continue to support academic excellence, research culture, and evolving educational demands.